Factors Determining High Performance Organizations within Small-scale Plastic Components Manufacturing Industry in India - Jayaraj, Balaji; Bhaumik, Amiya (International Journal of Psychosocial Rehabilitation, 2020)
The World Economic Forum in the very recent global competitiveness report found that India is ranked 39th out of 138 countries globally. Having the “population of 1292.7 (millions), GDP 2090.7 (US billions), GDP per capita 1617.3 (US), GDP (PPP) % World GDP 7.02." It is understood from the global competitiveness report that during the year 2012-2013, India was ranked 59th out of 144 countries, and from then on, India has improved their performance and is currently in the 38th rank in 138 countries globally [1].